A fast-growing dengue virus mutant reveals a dual role of STING in response to infection. Issue 12 (14th December 2022) - Ng, Wy Ching; Kwek, Swee Sen; Sun, Bo; Yousefi, Meisam; Ong, Eugenia Z.; Tan, Hwee Cheng; Puschnik, Andreas S.; Chan, Kuan Rong; Ooi, Yaw Shin; Ooi, Eng Eong
Abstract : Abstract : The four dengue viruses (DENVs) have evolved multiple mechanisms to ensure its survival. Among these mechanisms is the ability to regulate its replication rate, which may contribute to avoiding premature immune activation that limit infection dissemination: DENVs associated with dengue epidemics have shown slower replication rate than pre-epidemic strains. Correspondingly, wild-type DENVs replicate more slowly than their clinically attenuated derivatives. To understand how DENVs 'make haste slowly', we generated and screened for DENV2 mutants with accelerated replication that also induced high type-I interferon (IFN) expression in infected cells. We chanced upon a single NS2B-I114T amino acid substitution, in an otherwise highly conserved amino acid residue. Accelerated DENV2 replication damaged host DNA as mutant infection was dependent on host DNA damage repair factors, namely RAD21, EID3 and NEK5. DNA damage induced cGAS/STING signalling and activated early type-I IFN response that inhibited infection dissemination. Unexpectedly, STING activation also supported mutant DENV replication in infected cells through STING-induced autophagy. Our findings thus show that DENV NS2B has multi-faceted role in controlling DENV replication rate and immune evasion and suggest that the dual role of STING in supporting virus replication within infected cells but inhibiting infection dissemination could be particularly advantageous for live attenuated vaccine development.